Linux fundamentals : video - Vugt, Sander van (LiveLessons (Indianapolis, Ind.), 2019)
You will start with Linux Fundamentals LiveLessons, a full video course on Linux basics, concepts, practices, and theories so you can get a foundational knowledge of Linux. Through the use of topic-focused instructional videos you will gain an in-depth understanding of Linux. The combination of demonstrations, white board instruction, and hands-on labs is a unique offering that gives you a full toolkit to enhance your learning, and provide a seamless path forward should you want to get certified for Linux Foundation CompTIA Linux+ or other entry-level Linux exams. Labs are presented at the end of each lesson, giving you the opportunity to test out the skills you have learned over the lesson. Sander then walks you through the Lab Solution to compare how you did.